If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4(4 + -4k) = 0 (4 * -4 + -4k * -4) = 0 (-16 + 16k) = 0 Solving -16 + 16k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '16' to each side of the equation. -16 + 16 + 16k = 0 + 16 Combine like terms: -16 + 16 = 0 0 + 16k = 0 + 16 16k = 0 + 16 Combine like terms: 0 + 16 = 16 16k = 16 Divide each side by '16'. k = 1 Simplifying k = 1
| x=-(-2)-(-2)-1 | | 7x+2-4x+8=24 | | x/18=neg3 | | 4g+g+9=39 | | 3(2x-1)+2=8x-2x-1 | | 25x+3y=90 | | -7/3w=-42 | | 1+4k=-23 | | 20/k=10 | | x=(y-1)/5 | | 6z-13=5 | | 2xsquared+12x+40=360 | | 5x-3+6x-8= | | 19=-5y+7+8y-3 | | 64.2=6(m+3.1) | | 9X+3=-X+13 | | 60=3(4n) | | 10x=9+14x | | 5(-7+7v)= | | 2671=p+r | | x+24+3x=-23-3x-30 | | 4x-5=1*5(5x+20) | | 6n+21=21n-15 | | -6(-7/2) | | 5(-7+7)= | | 18p-27=13 | | 4/4b=2/6-5 | | 23-5x=12+4x | | 4a^4b^2c/12a^2b^-5c3 | | P/10=-2/8 | | 2+7*10-3=51 | | 2x+3y-6z=42 |